Linguistic Modality and Female Identity in Chaucer’s Clerk’s Tale - Stadnik, Katarzyna (Studia Anglica Posnaniensia, 2016)
While exploring the situated nature of conceptual knowledge, the paper investigates the linguistic construction of identity relative to the language user’s sociocultural situatedness, which is regarded as a derivative of the continuity of language and culture. In this functionally-oriented study, we examine how the situatedness of the language user affects their expression of the selves, which in the article we construe in terms of social roles performed by men and women in a specific cultural community. Importantly, we claim that, although the data are historical in nature, they nevertheless help us address the problem of the elusive nature of human identity, a theme recurring in the linguistic study of subjectivity. We seek to explore the general question of experiential motivation behind the frequency patterns of linguistic usage. We illustrate the issue by referring to the historical data taken from Geoffrey Chaucer’s Clerk’s Tale. The poet’s use of selected modal verbs is contextualized in relation to the late medieval community of his present. We account for the poet’s usage of shul, mot- (in the sense ‘must’), o(u)ght(e), as well as mouen ‘may’, and willen, indicating the need for a more nuanced approach to the way in which the key modal notions of NECESSITY/OBLIGATION are applied in the study of linguistic modality. We thus advocate the adoption of a situated view of the abstract concepts. Furthermore, we argue that the usage patterns concerning the frequency with which the selected modal verbs are used in specific contexts of Chaucer’s narrative might be indicative of the ways in which the identity of a community member was negotiated in the late medieval society of the poet’s present. In conclusion, we indicate the challenges to present-day pragmatic research into the linguistic construction of identity. Specifically, the emphasis is laid on how findings from recent research into situated and social cognition can inform a pragmatic investigation of linguistic subjectivity.